Back Cover: Improved Biocompatibility of Black Phosphorus Nanosheets by Chemical Modification (Angew. Chem. Int. Ed. 46/2017). Issue 46 (13th October 2017) - Qu, Guangbo; Liu, Wei; Zhao, Yuetao; Gao, Jie; Xia, Tian; Shi, Jianbo; Hu, Ligang; Zhou, Wenhua; Gao, Jiejun; Wang, Huaiyu; Luo, Qian; Zhou, Qunfang; et al.
Abstract : Ultrasmall black phosphorous nanosheets (BPs) can trigger systemic inflammations. In their Communication on page 14488 ff., X.‐F. Yu, G. Jiang, et al. report a method to reduce this side effect by surface modification of bare BPs with titanium sulfate (TiL4 @BPs). The girl represents a potential candidate exposed to bare BPs through various routes during a wide application of this material. The effect of the bare BPs is shown by red shading. The BPs are less harmful after conversion to TiL4 @BPs.